(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Network safety alludes to the cluster of advances, cycles, and practices meant to make sure networks, gadgets, projects, and data from assault, harm, or unapproved access. Network safety might likewise be alluded to as information innovation security. Network safety is important on the grounds that administration military company financial and clinical associations gather interaction and store fantastic measures of data on PCs and completely different gadgets. A important phase of that data may be delicate information whether or not that be licenced innovation financial data individual information, or different types of data that unapproved access or openness might have negative results. In our methodology is we are able to discover the assault sorts utilizing in profound learning techniques.